PENGARUH LINGKUNGAN KERJA NONFISIK DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT ALMEGA NATA SARANA BALARAJA - Shelawati; Rizka Akbar, Irfan (Journal of Research and Publication Innovation, 2024)
The research was conducted at PT Almega Nata Sarana Balaraja using a quantitative associative method. The purpose of this study is to determine the effect of the nonphysical work environment (X1) and work stress (X2) on employee performance (Y) at PT Almega Nata Sarana Balaraja. The population of this study consisted of 79 employees, and the sampling method used was a saturated sample (census), meaning the entire population was used as the sample, totaling 79 employees. The results showed that the variables of non-physical work environment and work stress had an effect on employee performance both partially and simultaneously. The multiple linear regression equation is Y = 24,206 + 0,443X1 – 0,124X2. Partially, the nonphysical work environment (X1) obtained a t-value (9,695) > t-table (1,992) with Sig. 0,000 < 0,05, meaning the hypothesis is accepted, and there is a positive and significant effect between the nonphysical work environment and employee performance. The work stress variable (X2) obtained a t-value (-9,486) > t-table (1,992) with Sig. 0,000 < 0,05, meaning the hypothesis is accepted, and there is a negative and significant effect between work stress and employee performance. Simultaneously, the F-value is 71,622 > F-table 3,117. With a determination coefficient of 0,653, this indicates that the variables of nonphysical work environment and work stress together contribute 65,3% to the employee performance at PT Almega Nata Sarana Balaraja, while the remaining 34,7% is influenced by other factors not explained in this study.